Association between change in serum uric acid and rapid decline in kidney function in China - Yu Li; Jinqian Luo; Xiaoyan Liu; Qiong Huang; Yun Xia; Yan Yang; Jing Wang (Scientific Reports)
Abstract While the elevation of serum uric acid (SUA) is acknowledged as a risk factor for chronic kidney disease, the independent extent to which variations in SUA levels are correlated with temporal changes in estimated glomerular filtration rate (eGFR) remains uncertain. In light of this uncertainty, our research endeavored to elucidate the temporal associations between change in SUA and rapid eGFR decline in China. In this longitudinal study of China’s middle-aged and elderly between 2011 and 2015, we analyzed 5421 individuals with complete SUA and eGFR data. Logistic regression was applied to evaluate the risk factors associated with a rapid eGFR decline (defined by a 5 mL/min/1.73 m2 decrease or falling to less than 15 mL/min/1.73 m2 by 2015), adjusted for age, gender, marital, residence, income, BMI, hypertension, diabetes, dyslipidemia, CRP, Hba1c, baseline eGFR and baseline SUA. Linear regression was used to evaluate the relationship between variations in SUA and changes in eGFR. After multivariable adjustments, the risk factors of a rapid eGFR decline included aging (OR per 1-year increase: 1.1, 95% CI 1.08–1.12, P < 0.001), being female, being single, having hypertension, a higher baseline eGFR, a higher baseline SUA (OR per-1 mg/dL increase: 1.68, 95% CI 1.48–1.90, P < 0.001), and increase in change in SUA (OR per-1 mg/ dL increase: 1.92,95% CI 1.71–2.16, P < 0.001). Pearson’s analysis showed a significant inverse correlation between SUA changes and eGFR decline, particularly pronounced in females, with correlation coefficients of − 0.349 for females and − 0.306 for males (95% CI − 0.347 to − 0.299, P < 0.001). A significant correlation was found between the change in SUA and the rapid decline in eGFR, with this association being particularly pronounced in females.